2009
DOI: 10.1111/j.1600-0528.2009.00465.x
|View full text |Cite
|
Sign up to set email alerts
|

Enamel defects and dental caries in 9‐year‐old children living in fluoridated and nonfluoridated areas of Auckland, New Zealand

Abstract: Reticulated water fluoridation in Auckland reduces the risk of dental caries but increases the risk of diffuse opacities in 9-year-old children. Guidelines and health-promotion strategies that enable children to minimize their risk to diffuse opacities yet reduce their risk of dental caries should be reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 15 publications
5
8
0
Order By: Relevance
“…Diffuse opacity alone and in association with demarcated opacity were the most prevalent defects and accounted for 35% of the observations as previously observed [Ekanayake and van der Hoek, 2003;Kanagaratnam et al, 2009]. This finding was corroborated by a cross-sectional study carried out in 3-to 5-year-olds which examined tooth buccal, lingual and occlusal surfaces for DDE [Lunardelelli and Peres, 2006] and by a longitudinal study in 1-to 3-year-olds in which the defects were more frequently observed on buccal surface (18.4%), than on the lingual (0.8%) and occlusal surfaces (5.9%) [Chaves et al, 2007].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Diffuse opacity alone and in association with demarcated opacity were the most prevalent defects and accounted for 35% of the observations as previously observed [Ekanayake and van der Hoek, 2003;Kanagaratnam et al, 2009]. This finding was corroborated by a cross-sectional study carried out in 3-to 5-year-olds which examined tooth buccal, lingual and occlusal surfaces for DDE [Lunardelelli and Peres, 2006] and by a longitudinal study in 1-to 3-year-olds in which the defects were more frequently observed on buccal surface (18.4%), than on the lingual (0.8%) and occlusal surfaces (5.9%) [Chaves et al, 2007].…”
Section: Discussionsupporting
confidence: 66%
“…The examination of plaque-free and dried tooth surfaces under good illumination in our study revealed a higher prevalence of children with DDE (48%) than those reported in other fluoridated areas under various condi-tions, such as clinical examinations carried out under natural light and without plaque removal [Weeks et al, 1993;Li et al, 1996;Lunardelli and Peres, 2006] and teeth examined in wet conditions [Hoffman et al, 2007;Kanagaratnam et al, 2009]. The DDE recording on buccal surfaces was used in our study since these surfaces represent the different periods of tooth formation reasonably [Milsom et al, 1996], have good accessibility and aesthetic importance [Fédération Dentaire Internationale, 1992], show the highest prevalence of developmental defects [Chaves et al, 2007] and are frequently combined with defects on occlusal surfaces.…”
Section: Discussionmentioning
confidence: 45%
“…The same results were concluded in a study performed on 9-year-old children in Auckland, New Zealand (27). They also reported that the main DDE type, the type that markedly increased in the area with higher fluoride concentration, was diffuse opacities.…”
Section: Discussionsupporting
confidence: 72%
“…The occurrence of DEO associated with EH —a condition commonly called Molar Incisor Hypomineralization, on the increase as well (4,10). Studies report DDE prevalence in developed countries and healthy children to be in the range of 24% to 49% in primary dentition, and 9% to 63% in permanent teeth (2,8,9,11-21). In Spain, the only studies of DDE prevalence in permanent teeth are limited to recording lesions in incisors and/or first molars (4,22).…”
Section: Introductionmentioning
confidence: 99%